2020
DOI: 10.1080/13552074.2020.1836817
|View full text |Cite
|
Sign up to set email alerts
|

Can we turn the tide? Confronting gender inequality in climate policy

Abstract: Emerging global crises such as climate change, massive migrations, pandemics, and environmental degradation are posing serious risks to humanity, threatening ecosystems and rural livelihoods across the globe. The poor, and especially the most marginalised among the poor, are disproportionately affected. Climate change in particular is expected to exacerbate pre-existing social inequalities, including gender inequalities. Therefore, innovative and equitable climate adaptation and mitigation strategies will be n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…In fact, many scholars stress that women (presumably also men) are not one homogenous group (Doss et al, 2018;Rao et al, 2019a). Therefore, gender quotas should be the minimum start to reaching equal shares of benefits from tree conservation and development outcomes (Cook et al, 2019), before moving beyond numbers to unpack relations of power, decision making and cultural beliefs (Rao et al, 2019b;Huyer et al, 2020). Instead, this study cautions against exaggerating gendered differences about tree preferences.…”
Section: Treementioning
confidence: 87%
See 1 more Smart Citation
“…In fact, many scholars stress that women (presumably also men) are not one homogenous group (Doss et al, 2018;Rao et al, 2019a). Therefore, gender quotas should be the minimum start to reaching equal shares of benefits from tree conservation and development outcomes (Cook et al, 2019), before moving beyond numbers to unpack relations of power, decision making and cultural beliefs (Rao et al, 2019b;Huyer et al, 2020). Instead, this study cautions against exaggerating gendered differences about tree preferences.…”
Section: Treementioning
confidence: 87%
“…The Koronivia Joint Work on Agriculture addresses the agriculture sector's roles in adapting to and mitigating climate change within the UNFCCC and considers Indigenous People's livelihoods and knowledge to be an integrated part of ecosystems (FAO, 2021). However, gender and social integration in climate policy has been slow globally, including the Nationally Determined Contributions (Huyer et al, 2020). In the 2016 NDCs, 64 out of 190 countries, all non-Annex I countries, refer to women or gender.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, despite the theoretical narrative of the capability of CSVs to enhance empowerment among the farmers, evidence to support this notion is rather patchy and scattered (Barnard et al, 2015) especially as a direct effect of the interventions at community levels. Yet the process of integrating gender issues into debates of policymaking around environment, climate change, agriculture and development has existed for quite some good time (Huyer et al, 2020). As FAO et al (2019) reported, this has partly been attributed to disproportionate focus on addressing ‘gender symptom’ instead of the causes of gender inequalities.…”
Section: The Climate-smart Village Approachmentioning
confidence: 99%
“…Despite increasing global policy efforts towards protecting the rights of rural women, and the prominent place of gender equality in the Sustainable Development Goals (SDGs), gender inequalities in the agricultural sector continue to be pervasive and are at risk of being exacerbated by the threats and constraints that climate change poses to rural populations [1]. These gender inequalities have important consequences not only for the women themselves, but for their entire families, communities and, ultimately, for the economic development of rural areas and of nations [2].…”
Section: Introductionmentioning
confidence: 99%
“…CSVs are sites of participatory testing and evaluation where researchers, local organizations and farmers work together to generate local evidence and draw out lessons to scale out and up CSA technical interventions (e.g., practices or services) and institutional interventions [10]. CSA interventions are based on three pillars: (1) sustainably increasing agricultural productivity of farmers, reflected in an increase of their income, food security and development; (2) enhancing adaptive capacity and building resilience to climate change; and (3) reducing and/or removing greenhouse gas emissions from agricultural activities, where possible [10][11][12].…”
Section: Introductionmentioning
confidence: 99%